1969
DOI: 10.1111/j.1432-1033.1969.tb19591.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Partial Characterization of a Carboxypeptidase from Barley

Abstract: A carboxypeptidase has been purified from germinated barley. The preparations are homogeneous in ultracentrifugal analysis. I n disc electrophoresis traces of impurities can be detected a t high concentration. The purified enzyme liberates carboxyl-terminal amino acid residues from a wide range of carbobenzoxy (Z)-dipeptides. Peptides containing proline are not attacked. It does not possess any endopeptidase, aminopeptidase, or dipeptidase activity. The enzyme has a pH optimum a t pH 5.2, is inhibited by di-is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
46
1
1

Year Published

1971
1971
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 17 publications
10
46
1
1
Order By: Relevance
“…conditions identical to those employed by RAY (38) and VISURE et al (43). From a Lineweaver-Burk plot, which did not deviate from linearity, a K m of 1.9 mM and Vma x of 1400 lamoles/min/mg was obtained.…”
Section: 1) (0)mentioning
confidence: 94%
“…conditions identical to those employed by RAY (38) and VISURE et al (43). From a Lineweaver-Burk plot, which did not deviate from linearity, a K m of 1.9 mM and Vma x of 1400 lamoles/min/mg was obtained.…”
Section: 1) (0)mentioning
confidence: 94%
“…This suggested the existence of five different enzymes which were termed carboxypeptidases I to V. Carboxypeptidase I was purified by VISURI et al (31) and carboxypeptidase II has been partially purified by YABUUCHI et al (34). From the ionic strengths at which the enzymes elute from a DEAE Sepharose column (see section 2.2.3) it is suggested that the enzyme previously isolated by our affinity chromatographic procedure (7) corresponds to malt carboxypeptidase I in MIKOLA'S nomenclature whereas the enzyme described in the present paper corresponds to malt carboxypeptidase II.…”
Section: Discussionmentioning
confidence: 99%
“…the conditions previously used to characterize purified or partially purified malt carboxypeptidases (28,31,34). From a linear LineweaverBurk plot a Km of 0.53 mM and Vm,x of 132 ttmoles 9 min"mg ~ was obtained.…”
Section: Enzymatic Properties Of Maltmentioning
confidence: 99%
See 1 more Smart Citation
“…These enzymes are also reported to be affected by di-isopropyl fluorophosphate (DIFP). [13][14][15][16][17] In view of the extreme toxicity, and consequent unavailability of this reagent, phenyl methyl sulphonyl fluoride (PMSF) which also inhibits active serinc residues, was used as a substitute. At a final concentration of 2mM, this reagent caused 34% inhibition of carboxypeptidase activity with N-CBZ-Phe-Ala.…”
Section: Enzymic Characteristicsmentioning
confidence: 99%